Control of Joint Property by Ex-Husband After Divorce in Banua Kepayang Village, Labuan Amas Selatan Sub-District, Hulu Sungai Tengah District - Hernayanti, Rini; Muhammad Fahmi Nurani (JOURNAL OF ISLAMIC AND LAW STUDIES, 2024)
This research is motivated by the problem of joint property controlled by the former husband after divorce in Banua Kepayang Village, Labuan Amas Selatan District, Hulu Sungai Tengah Regency. In this case, when a divorce occurs, the joint property is controlled by the former husband. It should be based on the Compilation of Islamic Law Article 97 states that "Widows or divorced widowers are entitled to one-half of the joint property as long as it is not specified otherwise in the marriage agreement." This type of research uses empirical legal research with a qualitative descriptive approach and a legal sociology approach. The data collection technique is done by interview. The data explored regarding the description of the control of joint property and the reasons behind the control of joint property by the ex-husband after divorce. The data source is informants with three former families. Data processing techniques through editing, categorization, description, and matrication. Data were analyzed using descriptive techniques. The results showed that the control of joint property was carried out by the ex-husband with a description of the joint property in each case varying. In the first case, the joint property was controlled entirely by the former husband. In the second case and the third case, the joint property was only partially controlled by the former husband by selling the joint property without distributing it to the former wife. There are several reasons behind the control of joint property. First, there is a signed agreement on stamp duty. Second, based on the understanding of the former husband that the former husband feels that he has contributed more in producing joint property, the existence of daily maintenance while still being husband and wife, iddah maintenance, and mut'ah maintenance, besides that because the former wife had cheated on him with another man when she was still a husband and wife. As according to the former wife, it was due to the ambition to fulfill all the wishes of the former husband such as buying a new car, a new motorcycle, building a house with a new wife, and others.